Unlocking lock-in. Emergence, perpetuation and decline of regional entrepreneurship in transitional societies: examples from contemporary Polandstrategy-as-practice - Grzegorz Simborowski; Paweł Kłobukowski (Rozwój Regionalny i Polityka Regionalna)
This paper examines how the phenomenon of lock-in can initially stimulate entrepreneurship and path creation in transitional societies but eventually impede municipal development. Focusing on three Polish municipalities – Łeba, Łęknica, and Tarnowo Podgórne – we investigate the factors that contribute to the persistence of lock-in and explore strategies to overcome it. Using qualitative analysis grounded in interviews with entrepreneurs, municipal authorities, and residents, and drawing on evolutionary economic geography, neo-institutionalism theory, and the strategy-as-practice approach, we analyze the interplay between geohistorical factors, entrepreneurial practices, and local government legitimacy. Our findings reveal that proactive entrepreneurs, when supported by responsive local governments, can redefine development strategies, foster diversification, and effectively break the lock-in cycle. This study underscores the critical role of collaborative efforts between entrepreneurs and municipal authorities in transforming regional development paths, offering valuable insights for policymakers in transitional economies.